2015
DOI: 10.1364/ol.40.004863
|View full text |Cite
|
Sign up to set email alerts
|

Photonic radio frequency phase-shift amplification by radio frequency interferometry

Abstract: We present a new technique for radio frequency (RF) phase-shift amplification based on RF interferometry and demonstrate it in an optical system. A striking feature of this amplifier is that the input phase noise is not amplified together with the input phase signal, so the phase sensitivity improves with higher phase amplification. We also predict that in the case of correlated amplitude noise, the sensitivity is not affected by the amplitude noise. With 600 MHz of modulated light and a phase amplification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Constructive interference may be achieved if the two signals are in phase; alternatively destructive interference is achieved if the phase offset between the two signals is ±π. The vector sum can also result in the change of the phase of the RF signal resulting in phase amplification 5456 . In practice, we achieved RF interference by encoding the RF signals into the optical domain using a modulation format with arbitrary amplitudes and phase in each sideband (achieved by using a phase modulator and a programmable optical filter) and mixing the processed signals through photodetection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Constructive interference may be achieved if the two signals are in phase; alternatively destructive interference is achieved if the phase offset between the two signals is ±π. The vector sum can also result in the change of the phase of the RF signal resulting in phase amplification 5456 . In practice, we achieved RF interference by encoding the RF signals into the optical domain using a modulation format with arbitrary amplitudes and phase in each sideband (achieved by using a phase modulator and a programmable optical filter) and mixing the processed signals through photodetection.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to an EIT resonance, a corresponding sharp phase slope resulting in an analogous slow-light effect 59 is also expected in this case. This is due to a vector-sum between two RF signals resulting in phase amplification 54 . The zeroes placed adjacent to the passband can increase the slope at the edges even further.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that a phase shift can be enhanced using interferometry [27][28][29]. However, so far these schemes have only been applied over a relative narrow bandwidth [27][28][29]. Here, on the other hand, we propose and demonstrate a phase enhancement scheme that has a broad bandwidth of sev-eral GHz through acting on the carrier.…”
Section: C)mentioning
confidence: 94%
“…So by applying a narrowband phase shift to the carrier, a broadband RF phase shifter can be achieved. It has previously been shown that a phase shift can be enhanced using interferometry [27][28][29]. However, so far these schemes have only been applied over a relative narrow bandwidth [27][28][29].…”
Section: C)mentioning
confidence: 99%